The impact of university of applied sciences teaching on the sustainability transition – case study on teachers’ abilities in sustainable development - Rummukainen, Maija (2025)
Universities of applied sciences play a significant role in promoting responsibility, as they are key actors in achieving sustainable development goals in society. Universities of applied sciences still have untapped potential to increase their impact in advancing the sustainability transition. Teaching plays a central role in this process, as it serves as a channel through which the values and knowledge of responsibility are passed on to future professionals. Integrating themes of responsibility into teaching supports students' ability to address complex environmental and societal challenges.